2010
DOI: 10.1111/j.1399-5618.2010.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of second‐generation antipsychotics in bipolar youth: comparison with other psychotic and nonpsychotic diagnoses

Abstract: There are early weight gain and metabolic changes across diagnoses in youth treated with SGAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 53 publications
4
26
0
1
Order By: Relevance
“…These data are consistent with previous results from much smaller European samples in which SGA-related weight gain was observed in mainly Caucasian adolescents with bipolar and psychotic disorders (Schimmelmann et al 2007;Arango et al 2009;Moreno et al 2010). In contrast, our sample consisted mainly of children with autistic spectrum disorders treated with risperidone.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data are consistent with previous results from much smaller European samples in which SGA-related weight gain was observed in mainly Caucasian adolescents with bipolar and psychotic disorders (Schimmelmann et al 2007;Arango et al 2009;Moreno et al 2010). In contrast, our sample consisted mainly of children with autistic spectrum disorders treated with risperidone.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, in European studies, an elevated risk of weight gain, obesity, and metabolic side effects has been reported in pediatric patients with bipolar disorder and psychotic disorders using SGAs. (Schimmelmann et al 2007;Arango et al 2009;Moreno et al 2010) On the other hand, European data are missing regarding the risk of overweight in pediatric populations with a psychiatric diagnosis with and without use of SGAs.…”
Section: Introductionmentioning
confidence: 97%
“…That was also the case for the combination with anticonvulsants, where sedation was found to be more frequent in patients on polypharmacy. However, it must be noted that most of these studies were of short duration, thus preventing the detection of some relevant long-term risks of the combination of SSRIs with SGAs and MSs such as metabolic AEs (Moreno et al 2010).…”
Section: Potential Risks Associated With Polypharmacy With Antidepresmentioning
confidence: 99%
“…Tan solo hay un número limitado de estudios, en su mayoría recientes, que han evaluado directamente el impacto de los ASG en estos componentes del SM en pacientes jóvenes. Los ASG que se asociaron a un mayor cambio de peso parecieron producir también los efectos más notables sobre la glucosa y los lípidos 25,93,98 .…”
Section: Efectos Adversos Metabólicos Y Componentes Del Síndrome Metaunclassified